(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This research investigates the impact of social media on small and medium-sized enterprises (SMEs), focusing on global trends and Uzbekistan’s experience from 2017 to 2025. The study analyzes how platforms such as Telegram, Instagram, and TikTok contribute to SME marketing, customer engagement, and business growth. By combining international literature with Uzbekistan’s digital transformation practices, the study provides a comprehensive understanding of social media’s role in SME development and offers recommendations for enhancing digital capability and competitiveness.